Common ownership and bank stability: Evidence from the U.S. banking industry - Park, Haerang; Oh, Byungmin (Journal of Financial Stability, 2022)
We empirically test competing theoretical arguments about the impact of common ownership on bank stability: the common ownership hypothesis, where banks decrease risk-taking by internalizing risk externalities on commonly held banks, and the diversification hypothesis, where banks increase risk-taking influenced by common owners who hold diversified portfolios and are less risk averse. Using data from the U.S. banking industry from 1991 to 2016, we find that banks with more common ownership linkages undertake lower risk, as predicted by the common ownership hypothesis. This relation is statistically significant and economically sizable, which is consistent across alternative measures of common ownership and bank risk and robust to potential endogeneity. Our study adds the financial stability perspective to the ongoing discussions on common ownership and antitrust regulations.